Studies on crystallization of lactose in permeates and the use of modified milk protein concentrate in high-protein dairy beverages - Pandalaneni, Karthik (Kansas State University, 2018)
Lactose is commercially produced from whey, whey permeate, or milk permeate as α-lactose monohydrate in crystalline form. Focused Beam Reflectance Measurement (FBRM) as a potential tool for in situ monitoring of lactose crystallization at concentrations relevant to the dairy industry was evaluated. Applicability of FBRM at supersaturated lactose concentrations 50%, 55%, and 60% (w/w) was reported in comparison with Brix values obtained from a Refractometer during isothermal crystallization at temperatures 20°C and 30°C. FBRM technique was shown to be a valuable tool for monitoring chord length distributions during lactose crystallization. In a different study, the influence of cooling rate during crystallization of lactose in concentrated permeates was studied. Three cooling rates accounting for approximately 17, 11, and 9 h were applied during lactose crystallization to evaluate the lactose crystal yield and quality of lactose crystals. There was no significant difference (P>0.05) found in lactose crystal yield, mean particle size obtained at the end of crystallization. This study suggested that increasing the cooling rate during lactose crystallization within the range explained in this study can save approximately 8 h of crystallization time. These studies evaluated FBRM as a potential tool to monitor lactose crystal chord lengths and counts. Also, process improvements were suggested to increase the productivity of lactose crystallization process by reducing the crystallization time. In chapters 5 and 6, calcium-reduced milk protein concentrates (MPCs) were used as an ingredient to improve the stability of high-protein dairy beverages. Heat stability increased significantly (P>0.05) in 8% protein solutions made from 20% calcium-reduced MPC. A significant increase in heat stability was observed in beverages formulated with 20% calcium-reduced MPC in the absence of chelating agent. In another study, it was evident that the dairy beverage formulation with 20% calcium-reduced MPC showed no sedimentation and age gelation indicating an improved storage stability. These studies confirmed that 20% calcium reduced MPC contributed towards improved heat stability and storage stability of the high-protein beverages.
Keywords: Lactose crystallization; Focused beam reflectance measurement; permeates; high-protein beverages; calcium-reduced MPC